Detecting and addressing eating disorders among individuals experiencing food insecurity: considerations for dietetic practice - Davis, Heather A.; Myers, Emily; Serrano, Elena; Misyak, Sarah (Frontiers in Nutrition, 2025)
In the United States, almost 10% of Americans will experience an eating disorder in their lifetime. Despite evidence that eating disorders occur across socio-economic backgrounds, the stereotypes of eating disorders being a disease of affluence persist. The experience of food insecurity, defined as limited or inconsistent physical and economic access to a sufficient amount and variety of nutritious food needed for a healthy life, is significantly associated with greater eating disorder symptoms. There are several reasons eating disorder symptoms may develop in people experiencing food insecurity, including food/benefit distribution cycles, shame, and weight bias. This Perspective highlights the relationship between food insecurity and eating disorders and provides informed recommendations specific to dietetic practice. Guidance is provided for Registered Dietitian Nutritionists (RDNs) in settings that serve individuals at risk of, or experiencing, food insecurity. RDNs should be informed on best practices for screening for eating disorders and providing appropriate referrals to eating disorder specific care, as well as encouraging realistic, achievable health behaviors, and using non-stigmatizing language.